SEAWEED CHRONICLE: SEBUAH PROYEK HIBRIDA ESTETIKA & INDUSTRI RUMPUT LAUT DI PULAU PARI, KEPULAUAN SERIBU, INDONESIA - Gabrielle Nadine Cahya Mulya; Alvin Hadiwono (Jurusan Arsitektur dan Perencanaan, 2021)
As an area close to Indonesia’s capital city, Thousand Island have both nature and human ecosystem problems. From a nature perspective, the high levels of carbon produced by human activities in the capital cause marine pollution and imbalance of the Java Sea ecosystem. Meanwhile, from a human perspective, the high dependence of the people of the Thousand Islands on the capital city to meet their daily needs has made it difficult for the quality of life and the local economy to develop. In addition, the Thousand Islands has potential to grow seaweed, but didn’t catch local people’s interest because of the low selling value due to a lack of knowledge on how to process seaweed properly. The author designed the ‘Seaweed Chronicle : An Industrial and Aesthetic Hybrid Project’ which aims to solve the problems of the Thousand Islands, especially Pari Island, with the principles of ecological architecture. The industrial program utilizes an abundance of seaweed commodities to be processed into daily necessities for the community to improve the quality of life. The application of the theme 'beyond ecology' in the form of a program to appreciate the aesthetics of seaweed, which aims to change the human perspective to appreciate and appreciate the existence of other creatures (not just objects that are enslaved, but as subjects that are equal to humans) so as to increase awareness of nature. The program details for the project are industrial workshops (processing seaweed into paper, plastics, fertilizers, building materials, and furniture), seaweed development galleries (consisting of painting galleries, aquariums, seaweed appreciation with light, sea waves, time travel, and reflection), restaurants, educational stages, and stalls selling seaweed products. The project can be enjoyed by the people of Pari Island as well as attracting tourists. Keywords: aesthetic; ecology architecture; industry; seaweedAbstrakSebagai daerah yang berdekatan dengan ibukota Jakarta, Kepulauan Seribu memiliki permasalahan ekosistem alam dan manusia. Dari segi alam, tingginya kadar karbon akibat aktivitas manusia di ibukota menyebabkan pencemaran laut dan rusaknya keseimbangan ekosistem Laut Jawa. Sedangkan dari segi manusia, tingginya ketergantungan masyarakat Kepulauan Seribu terhadap ibukota Jakarta untuk memenuhi kebutuhan sehari-hari menyebabkan kualitas kehidupan dan ekonomi setempat sulit berkembang. Selain itu, Kepulauan Seribu memiliki potensi budidaya rumput laut, namun kurang diminati masyarakat karena nilai jual rendah akibat kurangnya pengetahuan cara mengolah rumput laut. Penulis merancang proyek ‘Seaweed Chronicle : Sebuah Proyek Hibrida Estetika & Industri Rumput Laut’ yang bertujuan menyelesaikan permasalahan Kepulauan Seribu, khususnya Pulau Pari, dengan prinsip arsitektur ekologi dan menyatukan fungsi estetika dan industri. Program industri memanfaatkan komoditas rumput laut yang melimpah untuk diolah menjadi barang kebutuhan sehari-hari masyarakat guna meningkatkan kualitas hidup. Penerapan tema ‘beyond ecology’ berupa program penghayatan estetika rumput laut yang bertujuan mengganti cara pandang manusia agar lebih menghayati dan menghargai keberadaan makhluk lain (bukan hanya sekedar objek yang diperbudak, namun sebagai subjek yang setara dengan manusia) sehingga meningkatkan kepedulian terhadap alam. Rincian program pada proyek adalah workshop industri (pengolahan rumput laut menjadi kertas, plastik, pupuk, material bangunan, dan furniture), galeri penghayatan rumput laut (terdiri dari galeri lukisan, aquarium, penghayatan rumput laut dengan cahaya, gelombang laut, perjalanan waktu, dan refleksi), restoran, panggung edukasi, dan kios penjualan hasil rumput laut. Proyek dapat dinikmati oleh masyarakat Pulau Pari sekaligus menarik wisatawan.